Re-Inventing Teachersâ Competences at Early Childhood Education in Building Characters Needed for Global Competition - Machmud, Karmila (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
The goal of this paper is to elaborate and to re-invent the competencies needed by early childhood education teachers. Building childrenâs character from an early age is significant, but the main problem that is often overlooked is the contribution of Early Childhood Education teachers. Childrenâs character formation is largely determined by the quality of early childhood teachers. So if we want to instill character values required by our nations, the improvement of the quality of early childhood teachers is very significant. In terms of shaping childrenâs character, they should be equipped with some important skills and competences, because they have a significant role in building the Indonesian Childrenâs characters needed in global competition without abandoning their identity as a dignified Indonesian.—–Tulisan ini bertujuan untuk menjelaskan dan menemukan kembali kompetensi yang harus dimiliki oleh guru PAUD. Pembentukan karakter anak usia dini sangat ditentukan dengan kualitas guru PAUD. Sehingga jika kita ingin menanamkan nilai-nilaikarakter yang dibutuhkan oleh anak bangsa kita, maka peningkatan kualitas guru PAUD sangatlah signifikan. Dalam hal pembentukan karakteranak, seorang guru PAUD harus dibekali dengan beberapa keahlian dan kompetensi, karena mereka bertanggung jawab untuk membentuk generasi Indonesia yang mampu berkarya di tingkat Internasional, tanpa meninggalkan identitasnya sebagai bangsa Indonesia yang bermartabat.